REVITALISASI ETIKA BISNIS DALAM MEMBANGUN SISTEM PEREKONOMIAN YANG BERADAB - Mu'min, Ma'mun (Universitas Islam Negeri Sunan Kudus, 2015)
The revitalization of business ethics in the global economic system today urged to be done given the global economic competition tend to justifies any with regard not business ethics. Business Ethics so very important done especially in arranging business relationship with the parties that are related with good nature, environment, companies and individuals. Do business with regard not the ethics of course willresult in injustice, evil and destruction, or at least no parties who are disadvantaged because of the fraudulent behavior. The revitalizationof business ethics in order to build the economy that civilized so urgent and urgent. Among the business ethics that must be were revitalized, namely values of honesty, trust responsible, moral courage, fairness, realistic and critical, humble respect for stakeholders.